The Mechanism of State Support for Automobile Industry in Ukraine Механизм государственной поддержки автомобилестроения в Украине - Kolbasin Yevgeniy S., (Problemi Ekonomiki, 2010)
The current legislation of Ukraine concerning the support of automobile production has been analyzed. The instruments of influence within the scope of methods of direct and indirect regulation of the automobile industry and the mechanism of its state support in conditions of crisis have been suggested. Проанализировано действующее законодательство Украины относительно поддержки автомобилестроения. Предложены инструменты влияния в рамках методов прямого и косвенного регулирования отрасли автомобилестроения и механизм ее государственной поддержки в условиях кризиса.